MEMS : fundamental technology and applications - Choudhary, Vikas; Iniewski, Krzysztof (Boca Raton : CRC Press,Taylor & Francis Group, 2013)
'Written by international experts, this book presents the latest research in the field of MEMS technology and the myriad applications that it has enabled. The text covers automotive, consumer, communication, and medical applications of MEMs. Some of the applications discussed include high-precision on-chip integrated oscillators for reference generations, gyroscopes in cameras for optical image stabilization, radio communication, bio-implantable kidneys, and mobile phones. Other chapters address MEMS packaging and MEMS resonators, providing a fundamental understanding to enable novel applications. There is also a chapter outlining the historical evolution of current nano micro systems'--
Includes bibliographical references and index.
Keywords: Microelectromechanical systems; Microelectronic packaging